Facebook as an educational tool in horizontal groups of university students: emotions and communication - Suárez Ramírez, José Carlos (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The objective of this research is to correlate communications and the emotional dimension, and to know the expressive variety used by university students in their horizontal groups on Facebook. A descriptive and longitudinal methodology is applied, collecting qualitative and quantitative information through observation. The study population is composed of 3,592 students during the scholar year 2015/16 and 2,756 in 2022. The results obtained indicate that the emotional dimension is present in student groups, and its usefulness for educational purposes, in Facebook, hence the desirability of using this social network in university education.